2019
DOI: 10.15420/ecr.2019.16.2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes and Cardiovascular Risk: Caution Waiting for Evidence

Abstract: Electronic cigarettes use is a growing trend in contemporary societies, with the propensity to compete with traditional tobacco smoking. Some preclinical studies demonstrated the toxic and detrimental effects of electronic cigarettes liquid components. Its impact on human health remains unknown and insufficiently studied. While some studies suggest that electronic cigarettes use might be associated with endothelial dysfunction, impaired platelet function and increased risk of adverse clinical events, other stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 107 publications
(97 reference statements)
0
24
0
1
Order By: Relevance
“…Though ENDS are promoted as a less harmful alternative to smoking, current evidence links their use to a wide range of deleterious health effects. A growing body of evidence supports the association between ENDS use and addiction ( Primack et al, 2018 ), cardiovascular disease ( D’Amario et al, 2019 ; MacDonald and Middlekauff, 2019 ), cancer ( Wu et al, 2020 ), and respiratory disease, including acute, and chronic lung damage ( Gotts et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though ENDS are promoted as a less harmful alternative to smoking, current evidence links their use to a wide range of deleterious health effects. A growing body of evidence supports the association between ENDS use and addiction ( Primack et al, 2018 ), cardiovascular disease ( D’Amario et al, 2019 ; MacDonald and Middlekauff, 2019 ), cancer ( Wu et al, 2020 ), and respiratory disease, including acute, and chronic lung damage ( Gotts et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In the US, for example, a recent study reported there were an estimated 2 million never-smoking e-cigarette users in 2016. 6 With the introduction of JUUL (a sleek, discreet, USB-shaped e-cigarette, especially popular among young people), these estimates are likely to be trending upwards. Given the cardiovascular health concerns that exposure to these substances raise, a critical public health question arises over the level of evidence that scientists, clinicians and policymakers should consider sufficient to inform healthcare decisions and regulatory policy.…”
mentioning
confidence: 99%
“…For now, the bulk of evidence is derived -as D'Amario et al correctly noted -from animal studies, acute exposure human studies and cross-sectional epidemiologic studies. 6 While these studies hint at potential cardiovascular toxicity, they are by no means definitive.…”
mentioning
confidence: 99%
“…D'Amario et al discuss the current evidence on the use of e-cigarettes for smoking cessation. 3 Smoking accounts for 11.5% of global deaths. The use of e-cigarettes has significantly contributed to a decline in classic cigarette smoking over the past decade and a recent randomised trial has shown that it is more effective for smoking cessation than nicotine-replacement therapy.…”
mentioning
confidence: 99%
“…5 As D'Amario et al state, more studies on the effects of e-cigarettes on CV but also general health are needed, but in the meantime, it is important to remember that 'no smoke' is better than 'electronic smoke'. 3 Carro et al address a different, yet similarly important, lifestyle issue that has a strong effect on CV health: nutrition. 6 The authors explore Behavioural Interventions to Reduce Cardiovascular Risk:…”
mentioning
confidence: 99%